The Roles of Calcium Ions in Parkinson's Disease: Calcium Channel Inhibitors as a Novel Agents? - Md Reyaz Alam; Khadga Raj; Shamsher Singh (MDPI AG, 2022)
Parkinson's disease (PD) is a neurodegenerative movement disorder characterized by the loss of dopaminergic neurons, which results in motor impairment. The rationale and objective of the review article is to determine whether CCBs use contributes to a lower risk of developing a first-time diagnosis of PD. Ca2+ homeostasis disruption and mitochondrial dysfunction play a vital role in PD aetiology. In addition, the L-type voltage-gated calcium channel is expressed at high levels amongst nigral neurons, and could play a role in the pathogenesis of PD. In the dopaminergic neurons, Ca2+ entry through plasma membrane Cav1 channels drives a sustained feed-forward stimulation of mitochondrial oxidative phosphorylation. This study investigates the therapeutic potential of R- and T-type Ca2+ channel inhibition in light of new preclinical and clinical data and the feasibility of available Ca2+ channel blockers to cure PD progression. The R-type calcium channel is a type of voltage-dependent calcium channel. Available findings suggest that calcium homeostasis in dopaminergic neurons might be a valuable target for developing new drugs for PD patients. The limitations of our study include reports of observational studies with different follow-up periods. The specific roles of individual drugs and doses were also not mentioned because of nonreporting in the studies.